The Development of Moodle Edukati-Based E-Learning Media in Badminton Learning to Enhance Students' Learning Independence and Digital Literacy - Ramly, Zamhary; Kamaruddin, Ilham; Adil, Ahmad; Hudain, Muh. Adnan; Hanafi, Suriah (Universitas Negeri Makassar, 2024)
This study is a Research and Development project using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The sample consists of 20 ninth-grade students. Data collection techniques include observation, questionnaires, and documentation. The results indicate that the developed media is considered valid, with a validation score of 1 from material and media experts using the Gregory test (very high validity). It is also categorized as highly practical based on teacher and student responses, with a practicality score of 94 (very practical). The Moodle Edukati-based e-learning media proved effective in enhancing students' learning independence and digital literacy, as evidenced by an N-gain score of 0.8 for learning independence and 0.74 for digital literacy, both in the high category. Therefore, it can be concluded that the Moodle Edukati-based e-learning media is suitable for use as a source and medium for independent learning and for training students' digital literacy skills.